Access of Web-OPAC in Engineering College Libraries in Karnataka: a Survey - Mulla, K. R.; Chandrashekara, M. (Journal of Information and Knowledge, 2013)
The research work is undertaken to study the effective use of Web Online Public Access Catalogue (Web-OPAC) in engineering college libraries in Karnataka. The main objective of the study was to examine the primary data is obtained from the cross section of user community through questionnaires. The importance of knowing the various search facilities available on effective use of integrated library software packages and their services, the engineering college libraries have started using advanced information technology in providing services to the users. Web-OPAC is one of the major services. The present study is an attempt to know the use of web-OPAC by the users. The study revealed that the tool is useful and at the same time respondents felt that there must be user orientation needed for the Web-OPAC, to help in retrieving the required documents. Examines the utilization and satisfaction of users about Web-OPAC and highlights the suggestions made by the users for the further improvement.